Comparison of sublingual buprenorphine and intravenous morphine in reducing bone metastases associated pain in cancer patients - Jamalian, Seyed Mohammad (Eur J Transl Myol, 2019)
Bone metastases is one of the most common causes of pain in cancer patients and have a significant effect on their quality of life. The most common symptom of bone metastases is pain that gradually develops. Morphine is used to relieve pain in these patients, but poorly accepted due to its adverse events. Therefore, the current study was aimed to compare the effect of sublingual buprenorphine, with certainly lower complications with morphine. Fourth patients were divided into 2 groups. In group A, metastatic cancer patients received 2.5 mg of intravenous morphine. Furthermore, in group B, sublingual tablet of buprenorphine (one-fourth of a 500 μg tablet) was administered sublingually. Pain was measured 15, 30, and 45 minutes after the onset of pain using visual analog scale ruler. Based on the obtained data, two groups A and B were compared using SPSS 23 software. There was a significant difference between the patient's pain intensity after 15 and 30 minutes from the onset of pain in both groups. Due to the fact that the duration of the effect of morphine is 3-4 hours and the duration of the effect of sublingual buprenorphine is 6-8 hours, morphine showed fast acting forms of opioids (P= 0.001). The required dose level on the first day was similar in both groups and there was no statistically significant difference between the two groups. While on the second and third days, the median dose in group A (morphine) was greater than group B (buprenorphine), indicating prolonged duration of action for buprenorphine compared with morphine, thus requiring lower subsequent doses. The results of this study suggested that sublingual buprenorphine is a higher effective drug compared to intravenous morphine during and after operation. With regard to easy and painless administration, it seems that its use can be useful in controlling pain due to bone metastases in cancer patients.